Pembinaan Nilai-nilai Karakter Kewirausahaan Siswa dalam Membangun Karakter Bangsa Indonesia - Pepi Erlinda; Maria Montessori (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
The purpose of this study was to examine the development of the entrepreneurial character values of students in building the character of the Indonesian Nation in the State Vocational High School (SMKN) 2 Lubuk Basung. These character values are creative, hard work, disciplined and honest. This research uses a qualitative method with a case study approach. Informants in this study were the principal, teachers, heads of departments and students. Data collected through interviews, observation and documentation. Data validity test is done by checking (triangulation) by checking the correctness of the data then comparing the data obtained from other sources. The data obtained were analyzed by referring to the Miles and Huberman analysis model with steps namely data reduction, data presentation and conclusion drawing (verification). The results of this study explain that coaching entrepreneurial character through entrepreneurial learning. The character form of honesty of students is to sell the results of their own practice by reporting the results to the teacher, doing assignments honestly. Discipline Character completes assignments and enters class on time, using practice clothes when practice. The character of hard work completing tasks in accordance with the specified time, looking for information relating to the given task. The creative character determines the product to be produced, resolves obstacles with its own abilities.